A new species of the genus Calotes Cuvier, 1817 (Squamata: Agamidae) from southern Vietnam - Hartmann, Timo; Geissler, Peter; Poyarkov, Nikolay Jr. A.; Ihlow, Flora; Galoyan, Eduard A.; Rödder, Dennis; Böhme, Wolfgang (Zootaxa, 2013)
We describe a new species of the agamid genus Calotes Cuvier, 1817 from southern Vietnam, which is most similar to Calotes mystaceus Duméril & Bibron, 1837, but can be distinguished from the latter and its other congeners by genetic and morphological differences. We discuss the current distribution of the new species and its sister species C. mystaceus in Mainland Southeast Asia.